Unending crisis : national security policy after 9/11 - Graham, Thomas, Jr., 1933- (Institute of Global and Regional Security Studies, Jackson School of International Studies in association with University of Washington Press, 2012)
From the publisher. In Unending Crisis, Thomas Graham Jr. examines the second Bush administration's misguided management of foreign policy, the legacy of which has been seven major -- and almost irresolvable -- national security crises involving North Korea, Iran, Afghanistan, Pakistan, Iraq, the Arab-Israeli conflict in Palestine, and nuclear proliferation. Unending Crisis considers these issues individually and together, emphasizing their interrelationship and delineating the role that the neoconservative agenda played in redefining the way America is perceived in the world today.